Demographic and clinical profile of vernal keratoconjunctivitis and testing of health related quality of life in a tertiary hospital in South India - Johnson, Steffy; Ignasious, Justin (International Journal of Research in Medical Sciences, 2020)
Background: Patient with vernal keratoconjunctivitis faces significant morbidity, which affects quality of life or; moreover, it can lead to vision threatening, corneal complication in severe cases and chronic cases coupled with potential iatrogenic side effects. Aim of this study to assess the demography, clinical features and quality of life of patients with vernal keratoconjunctivitis in a centre in South India. Methods: General objective is to access the health related-quality of life and demographic study of VKC patients in a tertiary eye care hospital in south India. KINDL questionnaire with 30 questions is used for 30 paediatric patients. Percentage analysis for clinical assessment and interpretation method for questionnaire was used as statistical method. Results: In clinical assessment papillary reaction (96.66%), giant papillae (83.34%), Horner Trantas dots (20%), shield ulcer (13.35%), corneal erosions (43.33%), conjunctival congestion (76.68%). In case of vision 36.66% had normal vision, 56.67% had mild vision loss, 6.68% with moderate vision loss. Conclusions: VKC affects the health related quality of life of the patients significantly. The management of VKC should consider this aspect of health related quality of life, in addition to clinical parameters. From the assessment of KINDL questionnaire 30 samples 18 patients had high and 12 patients had average quality of life.